Environmental Awareness on Beef Cattle Technology - Bamualim, Abdullah M; Thalib, A; Anggraeni, Y N; ., Mariyono (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
The acceleration program to meet beef self sufficient in 2010 is expected to increase animal protein consumption of Indonesian people in order to be equal with other countries as well as to improve the livestock farmerâs income. The main objective of the program is to increase cattle population. Since the availability of forage and grassland is limited, beef cattle development is driven to the crop and plantation integration approach by using their by-product as cattle feed. Crop and plantation by-products, generally are considered to be fiber source with high lignocelluloseâs and low nutritive value. Feeding high fiber would increase methane gas production, and faeces and grass cultivation also contributed on greenhouse emission. Methane is one of the main greenhouse gases contributed by agriculture sector; increasing beef cattle population using high fiber feed is predicted to increase methane production. Good management is expected to improve productivity and to reduce methane production on livestock. Some efforts could be done such as good feeding management and nutrition manipulation, environment friendly Â cattleÂ  wasteÂ  management,Â  improvingÂ  management onÂ  roughageÂ  cultivation, Â andÂ  improvingÂ  managementÂ  onÂ  cattle production. Â  Key words: Beef cattle, agricultural by product, methane, global warming